2015
DOI: 10.5455/2349-3291.ijcp20150511
|View full text |Cite
|
Sign up to set email alerts
|

Depression among mothers of autistic spectral disorder children

Abstract: INTRODUCTION Autism is a worldwide disorder 1 defined as severe psychiatric disorder of childhood marked by severe difficulties in communication and forming relationships with other people, in developing language, repetitive, and limited patterns of behaviors and obsessive resistance to small changes in familiar surroundings. 2 These signs all begin in children before the age of 3 years. 3 It affects information processing in the brain by altering how nerve cells and their synapses connect and organize; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…This finding was in agreement with the study of Al Towairqi et al. [ 28 ], in Taif region, Saudi Arabia, who demonstrated that Saudi mothers caring for ASD child were facing more depression compared to a group of mothers caring for normally developing children. They stressed that Saudi mothers of ASD children must be provided with definite psychological support and social interventions from both the government and private society to reduce the possibility of maternal depression.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in agreement with the study of Al Towairqi et al. [ 28 ], in Taif region, Saudi Arabia, who demonstrated that Saudi mothers caring for ASD child were facing more depression compared to a group of mothers caring for normally developing children. They stressed that Saudi mothers of ASD children must be provided with definite psychological support and social interventions from both the government and private society to reduce the possibility of maternal depression.…”
Section: Discussionsupporting
confidence: 93%
“…The Farsi version of MCMI-III has acceptable validity and reliability like the original version. In an Iranian study, the diagnostic validity of Farsi version was reported to be between 0.58 and 0.83 for all the scales of MCMI-III [18]. In the current study, Cronbach's alpha coefficient for reliability of subscales was between 0.68 and 0.86.…”
Section: Millon Clinical Multiaxial Inventory-iii (Mcmi-iii)supporting
confidence: 44%
“…According to the Centers for Disease Control and Prevention (CDC), ASD rose from 1 out of 150 children in 2000, 1 in 68 in 2012, to a striking 1 in 59 children in 2018 3 . Currently, Management of ASD is limited to aggressive behavioral therapies focused on increasing independence and reducing major ASD characteristics 4 . Therefore, more research is urgently needed to understand the genetics and possible environmental cofactors, which may play a role in ASD development.…”
Section: Introductionmentioning
confidence: 99%